Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Unit Damkar Denmabesad - Dyah Pratiwi; Supardi Supardi; Agus Dharmanto (Universitas 45 Surabaya, 2024)
This research aims to measure the influence of leadership style and work motivation on employee performance at the Denmabesad Damkar Unit. This research was conducted using descriptive quantitative methods. The number of samples used in this research was 100 respondents and processed the results of the respondent data using saturated samples with the Classical Assumption Test method. And Hypothesis Testing T Test, F Test. The software used in this research uses IBM SPSS 26. The results of this research show that the T X1 test on Y has a significance value of 0.01 < 0.05. Ho is rejected and Ha is accepted, which means that there is an influence of leadership style on employee performance in the Denmabesad firefighting unit that (1) leadership style has a significant effect on employee performance in the Denmabesad firefighting unit, (2) work motivation has a significant effect on employee performance in the Denmabesad firefighting unit, ( 3) Leadership Style and Work Motivation together have a simultaneous effect on Employee Performance at the Denmabesad Fire Department Unit.